Extreme events in the sedimentary record of maar Lake Pavin: Implications for natural hazards assessment in the French Massif Central. (1st June 2016) - Chassiot, Léo; Chapron, Emmanuel; Di Giovanni, Christian; Albéric, Patrick; Lajeunesse, Patrick; Lehours, Anne-Catherine; Meybeck, Michel
Abstract: A set of sedimentary cores, high resolution swath bathymetry and subbottom profiler data provides new insights on sedimentary processes in meromictic maar Lake Pavin, France. Three sedimentary environments (i.e., littoral, plateau and basin) have been identified in the lake from sediment composition using bulk organic geochemistry and the analysis of hydroacoustic images. Various forms of rapidly deposited layers (RDLs) have been identified and radiocarbon dated. An up to date stratigraphy of sedimentary events matching coeval RDLs across the lake is presented and illustrates a wide range of natural hazards linked to Lake Pavin during the last 2000 years. In AD 600, a sudden lake outburst triggered a slump deposit along with a 9 m lake-level drop that drove shifts in sedimentary organic matter composition. Outside the lake, outburst flood deposits have been described downstream and provide sedimentary evidence for this event. The lake-level drop also favored the generation of gravity reworking processes, as shown by (1) a regional earthquake-triggered large slope failure on the plateau connected to a mass-wasting deposit in the basin dated to AD 1300, and (2) a succession of turbidites in AD 1825 and AD 1860 contemporaneous to two historic earthquakes, suggesting that this lake is sensitive to earthquakes with a minimum epicentral intensity of V. Finally, past observations of lake water color changes in AD 1783 and AD 1936, similar to reports in other meromictic lakes, match iron-rich deposits identified in maar lake sediments and suggest that Lake Pavin could have undergone limnic eruptions. Highlights: 600 CE crater outburst triggered a sedimentary slump and an outburst flood. 1300 CE regional tectonic event generated a large slope failure in the basin. Two earthquake-triggered turbidites occurred during the XIXth century. Two historical limnic eruptions are contemporaneous with three iron-rich deposits.